VARIATION IN ESSENTIAL OIL COMPOSITION OF BOSWELLIA CARTERII BIRDW. AND ITS ANTIMICROBIAL ACTIVITY - Kamatou, G. P.; Viljoen, A.; van Vuuren, S.; Balwanth, P.; Gosai, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Boswellia carterii (Burseraceae) is used in traditional medicine, the cosmetic industry and in aromatherapy in many countries all over the world. This plant produces the lucrative commercial oil known as Frankincense oil which has a woody, spicy and haunting smell. Frankincense oil has several pharmacological properties and these include the promotion of the growth of skin cells, healing sores and wounds. Variation in the chemical composition of this oil has been reported in the literature. This prompted an investigation to study the commercial Frankincense oils from various suppliers. Twenty essential oils were analyzed by gas chromatography coupled to mass spectrometry. Most of the oils were qualitatively similar when looking at the major components. However, there was some significant quantitative variation. The major components that were identified in the oils included á-pinene (2-64%), á-thujene (1-33%); â-pinene (0.3-13%); myrcene (1-9%); sabinene (2-7%); limonene (1-20%); p-cymene (3-17%); â-caryophyllene (0.1-8%). The antimicrobial activity of the oils was investigated on gram-positive (Staphylococcus aureus and Bacillus cereus) and gram-negative bacteria (Escherichia coli and Proteus vulgaris) as well as on a yeast (Candida albicans). Efficacy ranged between 1.5-32 mg/mL, depending on the test organisms studied. The highest sensitivity was observed against B. cereus.